RANCANG BANGUN WEBSITE UNTUK MENDIAGNOSA KERUSAKAN MOTOR INJEKSI MENGGUNAKAN METODE FORWARD CHAINING - Fajar Alfiansyah; Chamdan Mashuri; Hadi Sucipto; Sri Widoyoningrum (Fakultas Teknologi Informasi, 2025)
This research aims to develop a website that can diagnose damage to injection motorbikes using the forward chaining method, with a case study carried out at the Zafran Motor Workshop. to this research is the increasing complexity of injection systems on motorbikes, which often makes it difficult for motorbike owners to identify and repair damage that occurs. The diagnosis process begins with receiving input of injection motor damage symptoms from the user through a friendly and easy to understand interface. The system uses the forward chaining method to evaluate the entered symptoms and develop existing rules to identify the cause of the damage. The diagnosis results are based on 43 symptoms, 27 types of damage, and 7 rules for diagnosing injection motor damage. This research succeeded in designing a website to diagnose injection motor damage using the forward chaining method The majority of respondents (84%) were very satisfied with the performance of this website, while 4% were satisfied, 8% were quite satisfied, and 4% were dissatisfied. Surveys show the majority find the website easy to use with an intuitive interface and clear instructions for use. Thus, this research produces an injection motor damage diagnosis website that is effective and reliable in determining the cause of damage accurately. The main contribution of this research is to provide a solution that makes it easier for users to diagnose injection motor problems independently, with reliable diagnostic results and a user-friendly interface. Key Word: Injection, diagnosis, forward chaining